Inactivation of the maize transposable element Activator (Ac) is associated with its DNA modification. - Chomet, P S (1987)
The Activator (Ac) element at the waxy locus (wx-m7 allele) has the ability to undergo changes in its genetic activity and cycles between an active and inactive phase. Comparison of active Ac elements at several loci and the inactive Ac at wx-m7 by Southern blot analysis revealed that the inactive Ac sequence was not susceptible to digestion by the methylation sensitive enzyme PvuII while active elements were susceptible to PvuII digestion. Restriction digest comparisons between the clones of the active and inactive Ac elements were indistinguishable. Further analyses with the enzymes SstII and the methylation sensitive and insensitive isoschizomers EcoRII and BstNI showed the inactive Ac sequence was methylated at these sites, whereas the active Ac was hypomethylated. Although the active Ac at the wx-m7 allele in different genetic backgrounds showed differences in the Ac DNA modification pattern, at least a fraction of genomic DNA contained Ac sequences that were unmethylated at all of the internal sites we assayed. These data may suggest a role for DNA modification in the ability of Ac to transpose from the waxy locus and to destabilize unlinked Ds elements.